Dosa Ketidakpedulian sebagai Kekerasan Pasif: Analisis Etika Kontemporer terhadap Sikap Edom dalam Obaja 1:10-14 - Deavy Stanley Tumuju; Unggun Maradona (Jurnal Teologi Berita Hidup, 2026)
This study aims to examine Obadiah 1:10-14 exegetically in order to show that Edom's indifference to Judah's suffering was a form of passive violence that in the perspective of Old Testament ethics was understood as sin, while actualizing its meaning for the social context and life of the church today. Very rarely has research examined apathy as a major sin, read Edom's actions as a form of passive violence, or developed a category of prophetic ethics based on "not helping" as a theological offense. In the perspective of Old Testament prophetic ethics, how can Edomi's indifference to Judah's suffering be understood as a form of passive violence? This research uses a qualitative approach with a literature study method on the Book of Obadiah 1:1-21, a study of the concept of violence in theology, the integration of Old Testament ethics, and dialogue with contemporary situation. The findings of the study show that God's punishment of Edom is rooted in "passive violence" that manifests through the escalation of sin, ranging from standing at a distance (apathy), rejoicing over brother's calamity (violation of relationships), to active involvement in looting and refugee harassment (opportunism). In conclusion, indifference to the suffering of others is a form of passive evil that moves into activity, and will receive God's judgment according to the law of just retribution.